Pesticide Toxicity Profile: Organophosphate Pesticides - Frederick M. Fishel (EDIS)
This document provides a general overview of human toxicity, provides a listing of laboratory animal and wildlife toxicities and a cross-reference of chemical, common, and trade names of many organophosphate pesticides registered for use in Florida. This document is PI-50, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 2005.